Relationship Between Kindergarten Organizational Climate and Teacher Burnout: Work–Family Conflict as a Mediator - Ji, Dongying; Yue, Yaping (Frontiers in Psychiatry, 2020)
Burnout in kindergarten teachers is influenced by individual factors, social factors, and organizational factors. Kindergarten organizational climate as an external work resource may cause teacher burnout when it cannot meet their work demands. To explore the mechanisms that underlie the effects of kindergarten organizational climate on teacher burnout, we investigated the mediating effect of work-family conflict (i.e., work interfering with family and family interfering with work) on the relationship between kindergarten organizational climate and teacher burnout. The study sample included 436 kindergarten teachers in Henan, China. The Chinese versions of the Kindergarten Organizational Climate Scale, Kindergarten Teachers Work-Family Conflict Scale, and Kindergarten Teachers Burnout Scale were tested. The results showed that kindergarten organizational climate was positively correlated with work-family conflict and teacher burnout. Work-family conflict was positively correlated with teacher burnout. Work-family conflict partially mediated the effects of kindergarten organizational climate on teacher burnout. The mediating effect of family interfering with work was significantly stronger than the mediating effect of work interfering with family. The results are discussed with respect to the general literature on the correlation between organizational climate, WFC, and burnout.